COACHING WOMEN IN PRODUCTIVE ECONOMIC ACTIVITIES (PEA) IN LAMONGAN REGENCY - Yahya, Anton Eko Yulianto (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
The purpose of coaching women in productive economic activities (PEA) through training in productive economic activities provide bythe Office of Women’s Empowerment and Child Protection of Lamongan Regency is to boost the economy and welfare of the family. The training in productive economic activities was followed by 45 participants consisting of: 1) female heads of family; 2) women with Productive Economic Activities; and 3) women victims of domestic violence. The training was provided by the methods of lecturing, question and answer, and pastry-making practice. Results of the training include: 1) the participants showed a willingness to manage productive economic activities at the family and group levels in their respective villages or kelurahan; 2) the participants with a business were enthusiastic enough to have knowledge of and implement marketing strategies appropriate for their business continuity; and 3) the participants gained additional skills for making pastries